2021
DOI: 10.3390/ijms22041770
|View full text |Cite
|
Sign up to set email alerts
|

Role of Site-Specific Glycosylation in the I-Like Domain of Integrin β1 in Small Extracellular Vesicle-Mediated Malignant Behavior and FAK Activation

Abstract: Integrin β1 plays an essential role in the crosstalk between tumor cells and their microenvironment. Aberrant N-glycosylation of integrin β1 was documented to alter integrin β1 expression, dimerization, and biological function. However, the biological function of site-specific N-glycosylation of integrin β1 on extracellular vesicles is not fully understood. In this study, we mutated putative N-glycosylation sites in different domains of integrin β1. Removal of the N-glycosylation sites on the I-like domain of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 33 publications
0
6
0
Order By: Relevance
“…Integrin β1 is a typical glycoprotein characterized by its distinct structural domains, including a plexin-semaphorin-integrin (PSI) domain, an integrin-epidermal growth factor (I-EGF) domain, an I-like domain, both upstream and downstream of the hybrid domain, and a β-tail domain [ 29 ]. We further explored which domain of integrin β1 mainly bearing sialic acids using our previous established breast cancer cells expressing integrin β1 with mutant N -glycosylation sites in distinct domains (Additional file 1 : Figure S14) [ 22 ]. Lectin blotting analysis unveiled a markedly lower α2,6-linked sialic acid level in hybrid domain mutant (termed Δ7–8 mutant) compared to which in the other three mutants (Additional file 1 : Figure S15).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Integrin β1 is a typical glycoprotein characterized by its distinct structural domains, including a plexin-semaphorin-integrin (PSI) domain, an integrin-epidermal growth factor (I-EGF) domain, an I-like domain, both upstream and downstream of the hybrid domain, and a β-tail domain [ 29 ]. We further explored which domain of integrin β1 mainly bearing sialic acids using our previous established breast cancer cells expressing integrin β1 with mutant N -glycosylation sites in distinct domains (Additional file 1 : Figure S14) [ 22 ]. Lectin blotting analysis unveiled a markedly lower α2,6-linked sialic acid level in hybrid domain mutant (termed Δ7–8 mutant) compared to which in the other three mutants (Additional file 1 : Figure S15).…”
Section: Resultsmentioning
confidence: 99%
“…Human full-length and site-directed mutant integrin β1 were constructed in our laboratory [ 22 ]. Full-length and mutant integrin β1 with flag tag were cloned into the pLVX-AcGFP-N1 plasmid (Takara; Shiga, Japan), and transfected into YTS-1 cells as described previously [ 18 ].…”
Section: Methodsmentioning
confidence: 99%
“…Introducing an N -glycosylation sequence (N303-I304-T305) located at the hybrid-I-like domain on β1 or β3 integrin stabilized the open conformation of integrins and activated the metal ion-dependent binding site, thereby increasing their affinity for ligands ( Luo et al., 2003 ). More recently, removal of N -glycosylation sites on the I-like domain of integrin β1 (N212, N269, and N363) suppressed focal adhesion kinase signaling and cell migration in both donor and recipient cells through extracellular vesicles ( Cao et al, 2021 ). As a result, we were interested to know whether modulation of N -glycosylation sites on α2 subunit may affect ligand binding affinity, heterodimeric formation of α2β1 integrin, and downstream signaling.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, there are examples where cancer cells modify EV surface glycosylation to impart various properties. Cao et al (2021) demonstrated that N-glycosylation of integrin β1 on EVs derived from highly metastatic triple-negative breast cancer cells (MDA-MB-231) enhances the migratory ability of recipient cells that take up EVs through FAK signaling, promoting metastasis through glycosylated proteins on EVs. Moreover, breast cancer cell-derived MVs carrying highly glycosylated extracellular MMP inducer (EMMPRIN) were found to stimulate cancer cell invasion through the activation of the p38/MAPK signaling pathway in recipient cancer cells ( Menck et al, 2015 ).…”
Section: Glycosylation Changes the Fate Of Evsmentioning
confidence: 99%